Implementation of COIL in mental health education: Outcomes of a collaboration between Spain and the United States nursing students - Hoa Bui Appel; María Cristina Martínez-Fernández; Elena Fernández-Martínez (University of Groningen Press, 2023)
Collaborative International Online Learning (COIL) provides students meaningful and valuable engagement with students in another country to reach the goals of academic programs at the participating institutions. The strategy has demonstrated benefits for nursing students, including the acquisition of self-awareness, empathy, cultural humility, and leadership skills. The aim of this study was to share the results of the partnership in a COIL project using digital technology between a university in the United States and a university in Spain. The goals of this collaboration were twofold: to expose students in the U.S. and Spain to an international experience on mental health and to provide a comparative view of their respective health care systems. The chosen technique focuses on perceptions of mental health and how mental health care is delivered in clinical settings. A total of 166 students took part in this experience. The virtual exchange allowed students and faculty to share best practices in caring for people with mental illness. Nursing students providing care to COVID-19 patients reflected on lessons learned during the pandemic and its impact on community mental health. Small group activities such as icebreakers, homework assignments, and reflections were used to share and compare experiences. Students completed COIL surveys, which demonstrated that students from both countries perceived learning gains using evidence-based best practices related to key nursing concepts in a mutually respectful virtual exchange. The results show a perceived increase in the comprehension of mental health-related content and enhancement of clinical practice. Therefore, the COIL methodology is a feasible option as it allows for an intercultural exchange with an in-depth examination of content from the learners and teaching perspectives. In addition, it prepares students to work in international teams virtually.